Embodied cognition and L2 sentence comprehension: an eye-tracking study of motor representations - Shiang, Ruei-Fang; Chern, Chiou-Lan; Chen, Hsueh-Chih (Frontiers in Human Neuroscience, 2024)
Introduction: Evidence from neuroscience and behavioral research has indicated that language meaning is grounded in our motor–perceptual experiences of the world. However, the question of whether motor embodiment occurs at the sentence level in L2 comprehension has been raised. Furthermore, studies on motor embodiment in L2 have been limited to the lexical and phrasal levels, often providing conflicting and indeterminate results. Therefore, this eye-tracking study aimed to explore the embodied mental representations formed for reading comprehension of L2 action sentences. It further aimed to identify which motor representations are formed for L2 action sentence comprehension and the extent to which these representations are motor embodied. Methods: Fifty-six advanced L2 learners undertook a Sentence–Picture Verification Task, during which their response times (RTs) and eye movements were recorded. Each sentence–picture pair depicted an action that either matched or mismatched the action implied by the sentence. The data analysis focused on areas of interest around the body effectors. Results and Discussion: RT in the mismatch condition indicated an impeding effect. Furthermore, fixations on the body effector executing an action lasted longer in the mismatch condition, especially in late eye-movement measures.